Implementasi Model Cooperative Learning Tipe Make and Match Dalam Meningkatkan Hasil Belajar - Imam Baihaki (Sekolah Tinggi Agama Islam At-Tahdzib Ngoro Jombang, 2023)
Abstract: There are many factors that cause low student learning outcomes. This factor is caused by a lack of student involvement in learning and a lack of application of learning models in class, so that students become passive and make students' understanding less than optimal. This problem can be overcome by using the make and match type cooperative learning model. The aim of this research is to describe the improvement in student learning outcomes through the make and match type cooperative learning model in fiqh lessons on the Idain prayer material. This research was carried out at MI Sabilil Mukarromah Bercak Cermee Bondowoso. This type of research is classroom action research (PTK) with the research subjects being all 16 class IV students, 6 male students and 9 female students. The data collection methods used are documentation, interviews, observation and tests. Through two cycles, in each cycle there are 2 meetings applying the Make and Match Type Cooperative Learning model. Implementing the make and match type cooperative learning model in Fiqh lessons can successfully improve student learning outcomes. In Cycle I, classical completion was 50%, while in Cycle II it rose to 81.25%. So, the increase in classical completeness is 31.25%.